1999
DOI: 10.1165/ajrcmb.20.4.3405
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cathepsin K in Lung Epithelial Cells

Abstract: Alveolar and bronchial epithelial cells have been shown to have regulatory functions in the maintenance of lung structure and function. Recent evidence supports the premise that these cells can synthesize a variety of extracellular matrix components in vitro, suggesting an active participation in connective tissue remodeling. Their possible role in extracellular matrix degradation, however, is less clear. This study addresses the question of whether alveolar and bronchial epithelial cells express the highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 37 publications
3
56
0
Order By: Relevance
“…Conversely to that observed for CCD-19Lu myofibroblasts, we detected Cat activity in IPF culture media. This residual proteolytic activity of IPF samples obtained from lung biopsies probably relied on the presence (in addition to fibroblastic cells) of some resident macrophages and epithelial cells that are the primary source of extracellular Cats (8,22,58,59). Nevertheless, as observed for the CCD-19Lu model, inhibition of cystatin C by siRNA drastically rescued (4 -5-fold) Cat B activity (p Ͻ 0.001) (Fig.…”
Section: Silencing Of Cat B Impaired Smad Signaling Pathway Of Ccd19lumentioning
confidence: 80%
“…Conversely to that observed for CCD-19Lu myofibroblasts, we detected Cat activity in IPF culture media. This residual proteolytic activity of IPF samples obtained from lung biopsies probably relied on the presence (in addition to fibroblastic cells) of some resident macrophages and epithelial cells that are the primary source of extracellular Cats (8,22,58,59). Nevertheless, as observed for the CCD-19Lu model, inhibition of cystatin C by siRNA drastically rescued (4 -5-fold) Cat B activity (p Ͻ 0.001) (Fig.…”
Section: Silencing Of Cat B Impaired Smad Signaling Pathway Of Ccd19lumentioning
confidence: 80%
“…The cathepsin K gene was considered to be exclusively expressed in osteoclasts. Recently, however, this gene was identified in various types of cells, including mononuclear cells, that may act as precursor cells for osteoclasts (26), macrophages (27), and epithelial cells (28)(29)(30)(31). Cathepsin K has been considered to be a key enzyme involved in the degradation of articular cartilage, at least in the advanced and/or end stages of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin K RNA levels have been reported to be higher in human lung tumors compared with normal lung by RT-PCR analysis (23). Cathepsin K is capable of degrading components of the ECM, including collagen type I, II, and IV, as well as elastin at neutral pH (24). Cathepsin K expression is found in the fibroblasts of patients with fibrotic lungs, and experiments in cathepsin K-null mice revealed that cathepsin K can prevent lung fibrosis in bleomycin-treated mice by contributing to ECM turnover (25).…”
Section: Discussionmentioning
confidence: 99%